Bisphenol A Regulates Sodium Ramp Currents in Mouse Dorsal Root Ganglion Neurons and Increases Nociception - Soriano, Sergi (Sci Rep, 2019)
17β-Estradiol mediates the sensitivity to pain and is involved in sex differences in nociception. The widespread environmental disrupting chemical bisphenol A (BPA) has estrogenic activity, but its implications in pain are mostly unknown. Here we show that treatment of male mice with BPA (50 µg/kg/day) during 8 days, decreases the latency to pain behavior in response to heat, suggesting increased pain sensitivity. We demonstrate that incubation of dissociated dorsal root ganglia (DRG) nociceptors with 1 nM BPA increases the frequency of action potential firing. SCN9A encodes the voltage-gated sodium channel Na(v)1.7, which is present in DRG nociceptors and is essential in pain signaling. Na(v)1.7 and other voltage-gated sodium channels in mouse DRG are considered threshold channels because they produce ramp currents, amplifying small depolarizations and enhancing electrical activity. BPA increased Na(v)-mediated ramp currents elicited with slow depolarizations. Experiments using pharmacological tools as well as DRG from ERβ(−/−) mice indicate that this BPA effect involves ERα and phosphoinositide 3-kinase. The mRNA expression and biophysical properties other than ramp currents of Na(v) channels, were unchanged by BPA. Our data suggest that BPA at environmentally relevant doses affects the ability to detect noxious stimuli and therefore should be considered when studying the etiology of pain conditions.